Consumption Baskets and Currency Choice in International Borrowing - Bengui, Julien (2012)
Most emerging markets do not borrow much internationally in their own currency, although doing that has been argued as an attractive insurance mechanism. This phenomenon, commonly labeled "the original sin", has mostly been interpreted as evidence of the countries' inability to borrow in domestic currency from abroad. This paper provides a novel explanation for that phenomenon: not that countries are unable to borrow abroad in their currency, they might not need to do so. In the model, the small prevalence of external borrowing in domestic currency arises as an equilibrium outcome, despite the absence of exogenous frictions or limits on market participation. The equilibrium outcome is driven by the fact that domestic and foreign lenders have differential consumption baskets. In particular, a large part of domestic lenders' consumption basket is denominated in domestic currency whereas all of foreign lenders' is in dollars. A depreciation of domestic currency, which tends to occur in bad times, is therefore less harmful to domestic savers than to foreign investors. This makes domestic lenders require a lower premium than foreign lenders on domestic currency debt. For plausible calibrations, this consumption basket effect can induce foreign investors to pull out of the domestic currency debt market.